Measurement and Improvement of Fresh Milk Supply Chain Performance (Case Study of XYZ Farmers Group, Bogor Regency) - R. Andhikasari; T. Djatna; Y. Retnani (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
The challenges in the small-scale dairy industry often stem from outdated business management practices and a lack of comprehensive performance evaluation. This study adopts a structural approach by analyzing the performance of the fresh milk supply chain within Farmers Group XYZ, located inBogor Regency. We employed the SCOR and AHP methods for our performance analysis. Data were garnered through questionnaires, interviews, and observations. The findings reveal that the overall performance of the fresh milk supply chain was moderate, with performance scores of 84.25% forfeed suppliers, 77.47% for Farmers Group XYZ, and 82.05% for consumers. Notably, areas requiring enhancement include reliability, responsiveness, and cost-efficiency. Consequently, we have developed strategic recommendations aimed at augmenting supply chain effectiveness. These include enhancing the transportation system to ensure timely deliveries (Reliability), shortening order fulfillment times and improving the flexibility to adapt to demand fluctuations (Responsiveness), and optimizing logistics and storage to reduce costs (Cost). Implementing these strategies will bolster collaboration and fortify relationships among suppliers, producers, and consumers, contributing to a more robust dairy industry.